SISTEM INFORMASI PENYEWAAN ALAT CAMPING MENGGUNAKAN ALGORITMA COLLABORATIVE FILTERING PADA TEMAN PIKNIK - Santoso, Heri; Nasution, Imam Fadli; Putri, Raissa Amanda (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Camping equipment rental management at Teman Piknik is currently still done manually, causing various obstacles in operational activities. Frequently occurring problems include inefficient data recording processes, difficulties in managing rental transactions, and the lack of a system capable of providing camping equipment recommendations to customers. These conditions can impact the quality of service decline and make it difficult for customers to choose camping equipment that suits their needs and preferences. Furthermore, manual data management also has the potential to cause recording errors, data loss, and delays in the information processing process. This study aims to design and build a web-based camping equipment rental information system that can support the data management process and rental transactions more effectively and structured. The developed system applies the Collaborative Filtering algorithm to generate camping equipment recommendations to customers based on similar user preferences. The system development process was carried out using the Waterfall model method with implementation using the PHP programming language and MySQL database. This system provides various features, such as customer data management, camping equipment data management, rental transactions, rental history, and transaction reports for the admin. The research results show that the system developed can improve efficiency in rental management, speed up the transaction process, and help customers choose camping equipment that best suits their needs and preferences. With this system, the camping equipment rental process at Teman Piknik is expected to be more effective, organized, and provide better service to customers.